Assessment of pulmonary arterial circulation 3 months after hospitalization for SARS-CoV-2 pneumonia: Dual-energy CT (DECT) angiographic study in 55 patients. (April 2021) - Remy-Jardin, Martine; Duthoit, Louise; Perez, Thierry; Felloni, Paul; Faivre, Jean-Baptiste; Fry, Stéphanie; Bautin, Nathalie; Chenivesse, Cécile; Remy, Jacques; Duhamel, Alain
Abstract: Background: During COVID-19, the main manifestations of the disease are not only pneumonia but also coagulation disorders. The purpose of this study was to evaluate pulmonary vascular abnormalities 3 months after hospitalization for SARS-CoV-2 pneumonia in patients with persistent respiratory symptoms. Methods: Among the 320 patients who participated in a systematic follow-up 3 months after hospitalization, 76 patients had residual symptoms justifying a specialized follow-up in the department of pulmonology. Among them, dual-energy CT angiography (DECTA) was obtained in 55 patients. Findings: The 55 patients had partial ( n  = 40; 72.7%) or complete ( n  = 15; 27.3%) resolution of COVID-19 lung infiltration. DECTA was normal in 52 patients (52/55; 94.6%) and showed endoluminal filling defects in 3 patients (3/55; 5.4%) at the level of one ( n  = 1) and two ( n  = 1) segmental arteries of a single lobe and within central and peripheral arteries ( n  = 1). DECT lung perfusion was rated as non-interpretable ( n  = 2;3.6%), normal ( n  = 17; 30.9%) and abnormal ( n  = 36; 65.5%), the latter group comprising 32 patients with residual COVID-19 opacities (32/36; 89%) and 4 patients with normal lung parenchyma (4/36; 11%). Perfusion abnormalities consisted of (a) patchy defects (30/36; 83%), (b) PE-type defects (6/36; 16.6%) with ( n  = 1) or without proximal thrombosis ( n  = 5); and (c) focal areas of hypoperfusion (2/36; 5.5%). Increased perfusion was seen in 15 patients, always matching GGOs, bands and/or vascular tree-in- bud patterns. Interpretation: DECT depicted proximal arterial thrombosis in 5.4% of patients and perfusion abnormalities suggestive of widespread microangiopathy in 65.5% of patients. Lung microcirculation was abnormal in 4 patients with normal lung parenchyma.